Physical activity patterns and gestational diabetes outcomes – The wings project. (June 2016) - Anjana, Ranjit Mohan; Sudha, Vasudevan; Lakshmipriya, Nagarajan; Anitha, Chandrasekaran; Unnikrishnan, Ranjit; Bhavadharini, Balaji; Mahalakshmi, Manni Mohanraj; Maheswari, Kumar; Kayal, Arivudainambi; Ram, Uma; Ranjani, Harish; Ninov, Lyudmil; et al.
Highlights: We assessed the PA patterns of pregnant women in India. The effect of WINGS-MOC for GDM care on PA and pregnancy outcomes was evaluated. Most pregnant women in India are sedentary and do not meet the guidelines for PA. The WINGS MOC helped to reduce sedentary behaviour in women with GDM. Recreational walking was associated with better neonatal outcomes. Abstract: Objective: To compare physical activity (PA) patterns in pregnant woman with and without gestational diabetes (GDM) and to assess the effects of an exercise intervention on change in PA patterns, blood glucose levels and pregnancy outcomes in GDM women. Methods: For the first objective, PA patterns were studied in 795 pregnant women with and without GDM. For the second objective, the Women in India with Gestational Diabetes Strategy-Model of Care (WINGS-MOC) intervention were evaluated in 151 women out of 189 with GDM. PA was assessed using a validated questionnaire and a pedometer. Changes in PA patterns, glycemic parameters and neonatal outcomes were evaluated. Results: Overall, only 10% of pregnant women performed recommended levels of PA. Women with GDM were significantly more sedentary compared to those without GDM (86.2 vs. 61.2%, p  < 0.001). After the MOC was implemented in women with GDM, there was a significant improvement in PA and a decrease in sedentary behaviour amongst women (before MOC, moderate activity: 15.2%, sedentary: 84.8% vs. after MOC-moderate: 26.5%, sedentary: 73.5%; p  < 0.001), and an increase in their daily step count from 2206/day to 2476/day ( p  < 0.001). Fasting 1 and 2-h postprandial glucose values significantly decreased ( p  < 0.001 for all). Sedentary behaviour was associated with a fourfold higher risk ( p  = 0.02), and recreational walking with 70% decreased risk, of adverse neonatal outcomes ( p  = 0.04) after adjusting for potential confounders. Conclusions: PA levels are inadequate amongst this group of pregnant women studied i.e. those with and without GDM. However, a low-cost, culturally appropriate MOC can bring about significant improvements in PA in women with GDM. These changes are associated with improved glycemic control and reduction in adverse neonatal outcomes.